Neuro-Inflammatory Response and Brain-Peripheral Crosstalk in Sepsis and Stroke - Bourhy, Lena; Mazeraud, Aurélien; Bozza, Fernando A.; Turc, Guillaume; Lledo, Pierre-Marie; Sharshar, Tarek (Frontiers in Immunology, 2022)
Despite recent therapeutic advances, ischemic stroke is still a leading cause of death and disability. There is renewed attention for the peripheral inflammatory signalling as a way for modulating post-ischemic neuro-inflammatory process. The immune-brain crosstalk has long been investigated for understanding the mechanisms of sickness behaviour. The latter is an adaptive autonomic, neuro-endocrine, and behavioural response to a peripheral inflammation. It is mediated by humoral and neural pathways that mainly involve the circumventricular and vagal nerve, respectively. In the present review, we address how sepsis and stroke can dysregulate this adaptive response, notably by impairing the central integration of the peripheral signalling but also the efferent control of the immune response. We highlight the potential role of the gut-brain and the brain-spleen signalling in stroke.